Effectiveness of an association of a cranberry dry extract, D-mannose, and the two microorganisms Lactobacillus plantarum LP01 and Lactobacillus paracasei LPC09 in women affected by cystitis: a pilot study - Vicariotto, Franco (Journal of clinical gastroenterology, 2014)
Urinary tract infections (UTIs) are the most common bacterial infection in women. Most UTIs are acute uncomplicated cystitis caused by Escherichia coli (86%). This study was undertaken to assess the effectiveness of an association of a cranberry dry extract, D-mannose, a gelling complex composed of the exopolysaccharides produced by Streptococcus thermophilus ST10 (DSM 25246) and tara gum, as well as the 2 microorganisms Lactobacillus plantarum LP01 (LMG P-21021) and Lactobacillus paracasei LPC09 (DSM 24243) in women affected by acute uncomplicated cystitis. Thirty-three premenopausal, nonpregnant women diagnosed with acute uncomplicated cystitis were enrolled in a pilot prospective study and completed the treatment protocol. Subjects were instructed to take 2 doses per day during the first month, and then to continue with 1 sachet per day until the sixtieth day. Nitrites and leukocyte esterase on urine dipstick testing were used as indicators of cystitis, with analysis performed at enrollment, after 30 and 60 days, and after 1 month of follow-up. Typical UTI symptoms, namely dysuria, frequent voiding of small volumes, urinary urgency, suprapubic pain, and gross hematuria were scored 0 to 3 and evaluated at each visit. Positive results for the presence of nitrites and leukocyte esterase were found in 14 and 20 subjects after 30 days and in 9 and 14 women after 60 days, respectively (P<0.001). At the end of the follow-up period, positive results for nitrites and leukocyte esterase were recorded in only 4 and 3 of 24 and 19 subjects (16.7%, P=0.103; 15.8%, P=0.325, respectively), with negative results after 60 days. Typical symptoms of cystitis, specifically dysuria, frequent voiding, urgency, and suprapubic pain were significantly improved as well. No significant differences were recorded in the incidence and severity of hematuria at any visit. The long-term ability of an association of cranberry, D-mannose, an innovative gelling complex, and the 2 microorganisms tested to significantly improve the uncomfortable symptoms reported by women with acute cystitis has been suggested.